MiR‐143 acts as an inhibitor of migration and proliferation as well as an inducer of apoptosis in melanoma cancer cells in vitro. Issue 9 (20th July 2020) - Nabipoorashrafi, Seyed Ali; Shomali, Navid; Sadat‐Hatamnezhad, Leila; Mahami‐Oskouei, Mahmoud; Mahmoudi, Javad; Sandoghchian Shotorbani, Babak; Akbari, Morteza; Xu, Huaxi; Sandoghchian Shotorbani, Siamak
Abstract: Melanoma is a serious form of skin cancers begins in the melanocyte. Micro‐RNAs are small noncoding RNA with 19 to 25 nucleotides in length involves in the regulation of a wide range of biological processes. MicroRNAs are affected by an aberrant epigenetic alteration in the tumors that may lead to their dysregulation and formation of cancer. Recently, dysregulation of numerous microRNAs has been reported in different types of cancer. The present study focused on the role of miR‐143 in carcinogenesis of melanoma cancer. Here, we evaluated the expression level of miR‐143 in three melanoma cell lines in comparison with the normal human epidermal melanocyte cell line. Then, miR‐143 gene plasmid transfected into the WM115 cell line, for having the lowest expression of miR‐143. In addition, the effect of miR‐143 transfection on mRNA and protein levels of metastasis‐related genes was performed along with MTT assay, wound healing assay, and flow cytometry. The results showed that mRNA and protein expression levels of metastasis‐related genes including MMP‐9, E‐cadherin, Vimentin, and CXCR4 have been reduced following transfection of miR‐143. Moreover, the results of the scratch test showed that miR‐143 re‐expression inhibited cell migration. Also, the role of miR‐143 in the induction of apoptosis and inhibition of proliferation by flow cytometry and MTT was confirmed. As a result, the present study showed that miR‐143 was involved in metastatic and apoptotic pathways, suggesting that miR‐143 acts as a tumor‐suppressor microRNA in melanoma cancer.